microRNAs Shape Myeloid Cell-Mediated Resistance to Cancer Immunotherapy - Daveri, Elena; Vergani, Elisabetta; Shahaj, Eriomina; Bergamaschi, Laura; La Magra, Stefano; Dosi, Michela; Castelli, Chiara; Rodolfo, Monica; Rivoltini, Licia; Vallacchi, Viviana; Huber, Veronica (Frontiers in Immunology, 2020)
Immunotherapy with immune checkpoint inhibitors can achieve long-term tumor control in subsets of patients. However, its effect can be blunted by myeloid-induced resistance mechanisms. Myeloid cells are highly plastic and physiologically devoted to wound healing and to immune homeostasis maintenance. In cancer their physiological activities can be modulated, leading to an expansion of pro-inflammatory and immunosuppressive cells, the myeloid-derived suppressor cells (MDSCs), with detrimental consequences. The involvement of MDSCs in tumor development and progression has been widely investigated and MDSC-induced immunosuppression is acknowledged as a mechanism hindering effective immune checkpoint blockade. Small non-coding RNA molecules, the microRNAs (miRs), contribute to myeloid cell regulation at different levels, comprising metabolism and function, as well as their skewing to a MDSC phenotype. miR expression can be indirectly induced by cancer-derived factors or through direct miR import via extracellular vesicles. Due to their structural stability and their presence in body fluids miRs represent promising predictive biomarkers of resistance, as we recently found by investigating plasma samples of melanoma patients undergoing immune checkpoint blockade. Dissection of the miR-driven involved mechanisms would pave the way for the identification of new druggable targets. Here, we discuss the role of these miRs in shaping myeloid resistance to immunotherapy with a special focus on immunosuppression and immune escape.